Electrocatalytic oxidation of ascorbic acid mediated by lithium doped microparticles Bi2O3/MWCNT modified glassy carbon electrode - Zidan, Mohammed; Tan, Wee Tee; Zainal, Zulkarnain; Abdullah, Abdul Halim; Goh, Joo Kheng (Electrochemical Science Group, 2010)
Use of a lithium doped Bismuth oxide and MWCNT modified glassy carbon electrode (Bi2O3/Li+/CNT/GC) enhance the oxidation current of ascorbic acid during cyclic voltammetry compared to bare GC and (Bi2O3 /Li+/ CNT) modified electrode. Peak potential was observed to shift slightly to less positive value by about 220 mV and current was significantly enhanced by about two folds. The sensitivity under conditions of cyclic voltammetry is significantly dependent on pH, temperature, electrolyte and scan rate. The result of scanning electron micrograph shows that the size increased slightly by < 1 μm after electrolysis using Bi2O3 /Li+/ CNT modified electrode. The detection limit of this modified electrode was found to be 50μM. The oxidation current of ascorbic acid decreased slightly after the first cycle and became stable with minor decreases after second cycle. It is therefore evident that the Bi2O3/CNT modified GC electrode possesses some degree of stability. Potential use of Bi2O3/CNT as a useful electrode material is therefore clearly evident.